2019
DOI: 10.1590/0100-29452019104
|View full text |Cite
|
Sign up to set email alerts
|

Growth and quality of mangosteen seedlings (Garcinia mangostana L.) in response to the application of humic acids

Abstract: The time of formation of mangosteen seedlings propagated by seeds can be considered as the biggest difficulty in the seedling production system of this species. Considering that the use of humic acids as a growth promoter has been well documented in some species, the objective of this work was to evaluate the growth of mangosteen seedlings in response to the application of humic acid (HA) doses extracted from vermicompost (0; 2; 20; 40; 200 mg C L-1). Growth rate was determined using the following variables: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This behaviour was important because it allowed for estimating the survival and establishment of seedlings in the field. Similar to a previous study the variable DBH of G. mangostana serve as an alternative for evaluating the quality of this species growth [22].…”
Section: Relationship Between Crown Diameter and Dbhmentioning
confidence: 66%
“…This behaviour was important because it allowed for estimating the survival and establishment of seedlings in the field. Similar to a previous study the variable DBH of G. mangostana serve as an alternative for evaluating the quality of this species growth [22].…”
Section: Relationship Between Crown Diameter and Dbhmentioning
confidence: 66%
“…The DQI showed the same values as the other characteristics in the corrected substrate. This indicator has been used to evaluate the quality of seedlings in some fruit trees (Pereira et al, 2018;Gomes Júnior et al, 2019). The increase in DQI is a reflection of the biggest growth indicators (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Humic substances (HS) have been used to supply nutrients and/ or stimulate the production of phytohormones that lead to root growth that the plant would otherwise not achieve (El-Hai et al, 2019;Qin & Leskovar, 2020a;Soteriou et al, 2021). Previous studies have demonstrated the effect of humic substances as seedling growth modulators, among other beneficial effects (Gomes Júnior et al, 2019;Qin & Leskovar, 2020a;Silva et al, 2022;Targino et al, 2023).…”
Section: Introductionmentioning
confidence: 99%